PENGARUH INFUSA DAUN KEMBANG BULAN (Tithonia difersifolia) PADA KECEPATAN PENYEMBUHAN LUKA BAKAR - mulyani, dwi (Jurnal Ipteks Terapan, 2018)
The aim of this investigation was a clinical evaluation of the accelerating effect of Tithonia difersifolia extract  on the burn wound healing in male Sprague-Dawley rats weighted 200-350. The  sample then extracted using wet rendering (infusa) method using aqua-dest as extractor. The subjects were nine male Sprague-Dawley rats devided in to three group (negative control, positive control and  experimental). Every group consist of three rats. Heated metal plat (d=2cm) used to get full thickness burn wound on dorsal rat part. Then, Tithonia difersifolia folium extract was given to wound healing(plannimetri method) for 14 days, negative control(aqua dest) 26 days and positive control (Bioplasenton) 20 days.  The results with analysis Anova showed that Tithonia difersifolia folium extract have significant effect (p < 0,05) to wound healing of rat models.